The Effectiveness of Project-Based Learning Through Spotify Podcasts Media in Teaching Speaking - Muhammad Ainul Yaqin; M. Labib Al Halim (Universitas Islam Lamongan, 2023)
This research was intended to measure the effectiveness of project-based learning on students speaking skillsthrough Spotify Podcasts as media of teaching speaking. The research design used in this research was a pre-experimental one-group pretest-posttest design with the quantitative method. This research design was treated with no control group.The research was conducted in the odd semester at eleventh grade of MA MambausSholihinGresik in academic year 2022 / 2023. The research took place on extra hours after school which was completed for 8 consecutive days, and the duration was 30 minutes in each meeting.The participants of this research consist of 25 students. The researcher used Paired Sample T-test to determine the results of hypothesis testing. Based on the data analysis and discussion of the research data that has been done, it can be concluded that the use of podcasts can affect students' speaking skills. The researcher found that the t-test value of pre-test and post-test was remarked significantly different. The p-value (probability value) was lower than α (0.00 < 0.05). It indicated that Project-Based Learning through Podcast on Spotify could give significant effect on students’ speaking skills.